Model Predictive Control of an autonomous wheelchair. Issue 1 (July 2017) - Ceravolo, Eugenio; Gabellone, Mauro; Farina, Marcello; Bascetta, Luca; Matteucci, Matteo
Abstract: This paper presents the development of a MPC architecture for an autonomous wheelchair, that aims at reaching a desired goal while considering physical actuator limitations, obstacle avoidance and comfort constraints. The controller has been designed in such a way that it can be easily applied to an existing commercial wheelchair, without the need for a redesign of the on-board motor controllers. Moreover, thanks to the introduction of an inner feedback linearizing loop, a linear MPC has been considered, allowing for an efficient real-time implementation of the control system. The experimental results show the effectiveness of the proposal, and demonstrate that MPC can be considered a promising control approach to develop autonomous vehicles.